Penerapan Metode Web Engineering pada Sistem Informasi Ruang Terbuka Hijau Dinas Pekerjaan Umum dan Penataan Ruang Kota Pagar Alam - Alfis Arif (Teknik Informatika Universitas Pamulang, 2020)
This study aims to produce a Green Open Space (RTH) information system of the Pagar Alam City Public Works and Spatial Planning (PUPR) using the Web Engineering method. Based on observations at PUPR Office Pagar Alam City, it is found that the delivery of information that is currently running is still manual by using brochures, pamphlets, banners, inefficient counseling, and not many people can receive information. Causing many domestic and foreign tourists who do not know the places of Green City Pagar Alam. This research uses the method of developing a Web Engineering system with the following steps: Costumers Communication, Planning, Modeling, Construction and Depeloyment. As well as using Google Maps as a search place. Based on the results of testing that the functionality of the information system can be run well without any obstacles from the process, testing is done using the Black Box method. With this information system, it useful to provide users with easy information about Green Pagar Alam City.